Pre-flight characteristics of Hecht vaults - Yeadon, M. R.; King, M. A.; Sprigings, E. J. (Journal of Sports Sciences, 1998)
This study reports the techniques used by gymnasts to perform the Hecht vault and compares them with techniques used for the handspring somersault vault (Takei and Kim, 1990). Our main aim was to establish how the pre-flight characteristics of the Hecht vault influence post-flight performance. Data were obtained on 27 elite gymnasts performing the Hecht vault at the 1993 Canadian National Championships using two-dimensional video analysis with the direct linear transformation (DLT) technique. The maximum height reached by the mass centre during post-flight was significantly correlated (P < 0.001) with the vertical velocity of the mass centre and the body angle at horse contact. The backwards rotation of the body was significantly correlated (P = 0.015) with the shoulder angle at horse contact. The competition score was significantly correlated (P = 0.043) with the body angle at horse contact and was also related to the maximum height of the mass centre during post-flight. For the Hecht vault, the gymnasts had longer, lower and faster pre-flights with slower rotation at horse contact compared with the handspring somersault vaults.